AICCRA project accelerates CSA/CIS scaling through agribusiness partnerships in Zambia - Dahl, Hauke; Kakwasha, Keagan; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
AICCRA Zambia project led by IWMI enters into a strategic partnership with ACDI/VOCA (https://www.acdivoca.org/about/at-a-glance/) (Accelerator video to SMEs: https://youtu.be/mTXpagVFhxA; Accelerator launch video: https://youtu.be/Ogzr7pAmNgs). This has created a wide stakeholder dialogue space for the private and public sectors to find possible partnership models for addressing problems of climate change affecting water and food security situation in the country. Five SME partnerships were awarded accelerator grants aimed at increasing access to climate information services to over 300,000 farmers in Zambia by 2023.